2021
DOI: 10.3390/ani11123458
|View full text |Cite
|
Sign up to set email alerts
|

Data-Based Variables Used as Indicators of Dairy Cow Welfare at Farm Level: A Review

Abstract: During the last years, the interest in data-based variables (DBVs) as easy-to-obtain, cost-effective animal welfare indicators has continued to grow. This interest has led to publications focusing on the relationship between DBVs and animal welfare. This review compiles 13 papers identified through a systematic literature search to provide an overview of the current state of research on the relationship between DBVs and dairy cow welfare at farm level. The selected papers were examined regarding their definiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In 2011, a review observed that only a few studies reported relationships between DBIs and measurements of resting comfort and animal behavior ( 38 ). On one hand, this was explained by a general lack of studies examining correlations between DBIs and behavior or resting comfort, as was also reported recently ( 25 ). On the other hand, the potential of herd data to detect problems in resting comfort and behavior was questioned ( 38 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In 2011, a review observed that only a few studies reported relationships between DBIs and measurements of resting comfort and animal behavior ( 38 ). On one hand, this was explained by a general lack of studies examining correlations between DBIs and behavior or resting comfort, as was also reported recently ( 25 ). On the other hand, the potential of herd data to detect problems in resting comfort and behavior was questioned ( 38 ).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the DBIs had to be calculable using data routinely available in Switzerland. To identify the DBIs, results from previous scientific literature ( 25 ) were used. These DBIs were supplemented with DBIs that are currently being used in other animal welfare projects or assessments, such as Q-check ( 26 ) or AssureWel ( 27 ), even if no peer-reviewed reports have yet been published for these projects or assessments.…”
Section: Methodsmentioning
confidence: 99%
“…For literature identification, search queries were made in the scientific databases PubMED, Web of Science, Scopus, CAB Direct and Science Direct, and identified publications were analyzed based on the PRISMA guidelines ( 17 ). Detailed methods of the literature review for the different animal species are described in Gebhardt-Henrich and Schlapbach ( 18 ), Lutz et al ( 19 ), Minning et al ( 20 ), and Zufferey et al ( 21 ). Subsequently, a preliminary set of promising indicators was compiled and discussed with stakeholders.…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature reviews and market analyses indicate that sensor technologies have a high potential in assessing animal welfare at the level of an individual animal (Buller et al, 2020;Gómez et al, 2021;Stygar et al, 2021). Routinely collected on-farm data have already been proven to be a useful source of welfare information in the dairy (e.g., Nyman et al, 2011;de Vries et al, 2014;Lutz et al, 2021) and pig (e.g., Stygar et al, 2020) sectors. Several studies suggest that recordings from slaughterhouses may provide useful information on animal wellbeing on farms (Vial, 2019).…”
Section: Introductionmentioning
confidence: 99%